Removal of heavy metals present in water from the Yautepec River Morelos México, using Opuntia ficus-indica mucilage - Silvia Viridiana Vargas-Solano; Francisco Rodríguez-González; Rita Martínez-Velarde; S.S. Morales-García; M.P. Jonathan (Environmental Advances, 2022)
In this work, the capacity of Opuntia ficus-indica (OFI) mucilage as a coagulant material for the removal of heavy metals (HM) present in water samples from the Yautepec River, Morelos Mexico, was studied. The functional groups of the OFI mucilage were identified by Fourier transform infrared spectroscopy (FTIR) before and after the removal process. Ten water samples were collected in different sites of the Yautepec River, some physicochemical properties were evaluated according to established norms, and all the water samples were within the permissible limits of pH (6.5-8.5) and conductivity (1500 μS/cm) for human consumption; however, they presented heavy metals, which were quantified by atomic absorption spectrophotometry (AAS). The study of removal of heavy metals from the water samples was carried out using OFI mucilage at different concentrations (87.5, 175 and 350 mg/L) using the jar method, and then the physicochemical characteristics as well as the final concentration of the HM were evaluated. The results showed that the OFI mucilage had a reduction of water turbidity greater than 70% and a removal capacity greater than 90% for iron (Fe) and manganese (Mn), and greater than 60% for chromium (Cr) and arsenic (As), and less than 40% for cadmium (Cd), nickel (Ni) and lead (Pb). These percentages showed a dependence on the initial pH conditions, the initial HM concentrations as well as the OFI mucilage concentration used. The changes in the FTIR spectra of the OFI mucilage after removal showed that the carbonyl, carboxyl and hydroxyl groups were those that acted in the removal of the heavy metals.